Critical points approaches to elliptic problems driven by a p(x)-Laplacian - Heidarkhani, S.; Ge, B. (Український математичний журнал, 2014)
We establish the existence of at least three solutions for elliptic problems driven by a p(x)-Laplacian. The existence of at least one nontrivial solution is also proved. The approaches are based on the variational methods and critical-point theory.